KAJIAN DUKUNGAN TEKNOLOGI BERDASARKAN KONSEP TECHNOLOGY ACCEPTANCE MODEL DAN DAMPAKNYA TERHADAP KINERJA PERUSAHAAN JASA KONSTRUKSI DI MALUKU - Jacob Tubalawony (Soso-Q : Jurnal Manajemen, 2017)
This analysis is the adoption of the use of the Technology Acceptance Model (TAM), which consists of three main variables, namely perceived ease of use (perceived ease of use), perceived usefulness (perceived usefulness), and acceptance of IT (IT acceptance). Analysis technique used is a model structure with respondents equition experts who work on construction planners services company. The results show an IT support to the perceived ease of use (perceived ease of use), perceived usefulness (perceived usefulness), and acceptance of IT (IT acceptance), each received can significant effect on a significant level of 0.05, and increasing impact on company performance . Expected to support the company's management regarding the software Auto Cad and Auto Stat can be perceived community benefits Keywords: Technology Acceptance Model, usefulness, ease of use, acceptance.